2019
DOI: 10.3389/fphys.2019.00782
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Fatigue on Eccentric Strength and Electromechanical Delay of the Knee Flexors: The Role of Training Status

Abstract: Purpose: To examine the effects of fatiguing isometric contractions on maximal eccentric strength and electromechanical delay (EMD) of the knee flexors in healthy young adults of different training status. Methods : Seventy-five male participants (27.7 ± 5.0 years) were enrolled in this study and allocated to three experimental groups according to their training status: athletes (ATH, n = 25), physically active adults (ACT, n = 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
11
1
1
Order By: Relevance
“…Our study also observed how fatigue affected the amateur-level group runners to a greater extent because the reductions in the SJ ( Figure 2 A) and CMJ ( Figure 2 C) heights were significantly more marked in this group. These results fall in line with what El-Ashker et al indicated [ 61 ], who found that the subjects with a higher level of training presented better neuromuscular function with fatigue. Nonetheless, these intergroup differences were not noted for either the ABK jump ( Figure 2 E) or developed power (W) in all jumps ( Figure 2 B,D,F).…”
Section: Discussionsupporting
confidence: 92%
“…Our study also observed how fatigue affected the amateur-level group runners to a greater extent because the reductions in the SJ ( Figure 2 A) and CMJ ( Figure 2 C) heights were significantly more marked in this group. These results fall in line with what El-Ashker et al indicated [ 61 ], who found that the subjects with a higher level of training presented better neuromuscular function with fatigue. Nonetheless, these intergroup differences were not noted for either the ABK jump ( Figure 2 E) or developed power (W) in all jumps ( Figure 2 B,D,F).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, two to three concentric and eccentric submaximal testing trials on the isokinetic device were performed during the familiarization session with upper and lower limbs of the dominant and non-dominant side at 120°/s to get accustomed to the testing protocol [ 24 , 25 ]. Before the testing and measurement trials (i.e., second session), participants performed 10 min warm-up using a cycle ergometer (Monark Exercise, Vansbro, Sweden) at a self-selected intermediate intensity workload, with a rating of perceived exertion (RPE) of 5–6 points on a 0–10 RPE scale, followed by 5 min of dynamic and static quadriceps and hamstring stretching [ 25 ]. For the upper limb muscles, 3–5 min of unloaded upper body cycling was performed using an upper-body cycle ergometer (Saratoga Cycle, Rand-Scot, CO, USA) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The included studies were variate in number of participants but similar in their sample population ages (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), who had a minimum of 6 months resistance training experience. It is important to highlight the impact that training status have upon muscle activation pattern, since familiarization with the movement could substantially modify muscle activation elicited during each exercise [49][50][51]. Furthermore, twelve of the studies had a male sample, while the rest combined both genders [34-36, 41, 43], and only two studies included exclusively females [39,40].…”
Section: Methodological Issuesmentioning
confidence: 99%